Ichneumons in Reunion Island: a catalogue of the local Ichneumonidae (Hymenoptera) species, including 15 new taxa and a key to species - Rousse, Pascal; Villemant, Claire (Zootaxa, 2012)
We revised the ichneumonid fauna of Reunion Island, where 17 species were hitherto recorded. One genus (Tariqia gen. nov.) and 14 species are newly described: Acrolyta dindar sp. nov., Campoplex techer sp. nov., Diaparsis ramassamy sp. nov., Dusona douraguia sp. nov., Eriborus cadjee sp. nov., Enicospilus vitry sp. nov., Enytus huet sp. nov., Paraphyllax mussar sp. nov., Phygadeuon nativel sp. nov., Pristomerus rivier sp. nov., Stenomacrus payet sp. nov., Tariqia stellaris sp. nov., Temelucha labusi sp. nov. and Xanthocampoplex huberti sp. nov.. Himertosoma aciculata (Seyrig, 1932), Itoplectis albipes evoluta (Benoit, 1957) and Megastylus mascarensis Benoit, 1957 are now considered as synonyms of, respectively, Himertosoma striata (Seyrig, 1932), Itoplectis albipes Seyrig, 1932 and Megastylus vagabundus Seyrig, 1934. Furthermore, the subspecies Echthromorpha agrestoria spinator (Fabricius, 1781) and Echthromorpha agrestoria macula (Brullé, 1846) are synonymized and raised to species level as Echthromorpha spinator (Fabricius, 1781). A catalogue is provided for 13 subfamilies, 36 genera, and 65 species of Ichneumonidae known to occur on Reunion Island, together with new distribution and/or host records for 28 species. A key to subfamilies, genera and species is also provided.